2012
DOI: 10.1590/s0034-71672012000400014
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento de enfermeiros da Estratégia Saúde da Família sobre resíduos dos serviços de saúde

Abstract: ReSUmOO estudo realizado aborda a problemática envolvendo os resíduos sólidos de serviços de saúde e a atitude do enfermeiro perante os aspectos relacionados ao gerenciamento e a conscientização ambiental. Participaram da pesquisa dez profissionais atuantes na Estratégia de Saúde da Família, dos municípios de Araputanga, Mirassol D'oeste e São José dos Quatro Marcos. Os dados foram obtidos através da aplicação de questionários, posteriormente analisados através do software Origin ® . Observou-se o nível de con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 7 publications
0
16
0
14
Order By: Relevance
“…In the surgery department of an university hospital in Egypt 14 , it was found that 29% of the nursing staff had a satisfactory notion of waste management. Nationally, a study directed to nurses of the Family Healthcare Strategy Program in the State of Mato Grosso 15 , found that only 20% knew the waste management steps.…”
Section: Introductionmentioning
confidence: 99%
“…In the surgery department of an university hospital in Egypt 14 , it was found that 29% of the nursing staff had a satisfactory notion of waste management. Nationally, a study directed to nurses of the Family Healthcare Strategy Program in the State of Mato Grosso 15 , found that only 20% knew the waste management steps.…”
Section: Introductionmentioning
confidence: 99%
“…7 It is needed, therefore, to discuss this theme during education, providing spaces for critical reflection and dialogue, in an attempt to mold the future professional practice. 6 The research has shown that nursing professionals identify the inadequate management of SWHS as a causer element of harm to both the environment and for public health, presenting notions of some of the steps in the management, of their relevance and implications, but these are notions that still show as fragmented and isolated.…”
Section: Resultsmentioning
confidence: 99%
“…The correct packaging of healthcare wastes avoids unnecessary exposure of workers to biological hazards and accidents, besides preventing the contact with living beings and the environment, facilitating an appropriate destination (1,5) .…”
Section: Discussionmentioning
confidence: 99%
“…358 of the National Environmental Council, 2005, established the harmonization among regulatory entities about healthcare waste, shifting the responsibility of management to generators with the adoption of a management plan for healthcare waste. Including in the documents a set of procedures to be developed for its management in order to reduce risks to health, thus preserving the public health, natural resources and the environment (5)(6) .…”
Section: Introductionmentioning
confidence: 99%